Perancangan Aplikasi Konversi File Musik Midi Menjadi Notasi Musik - Ardi Syawaldipa; Youllia Indrawaty Nurhasanah; Muhammad Ichwan (SOTVI - Society of Visual Informatics, 2022)
Musical notation is a system of musical works that serves to document a person's musical works, which are generally written using block notation and number notation. The notation standard used by the international community is the block notation. However, for some musicians, reading musical notes is relatively more difficult than reading numerical notes. This causes the conversion that is done manually to be less effective. Therefore, in this study, an application was developed that functions to convert midi music files (file formats containing digital instruments) into notation. With this application, users can create their own sheet music from midi music files automatically, and the conversion results can be played back to find out how the song is playing. The input received by the system is a music file in midi format. While the output produced is musical notes and numeric notes in text format